Genetic diversity of MPOB-senegal oil palm germplasm based on quantitative traits and microsatellite markers - Myint, Khin Aye (2019)
Understanding the genetic structure of different vegetative, yield and yield component traits plays a major role in oil palm breeding program. Evaluation of genetic diversity based on morphology and physiology is insufficient to get comprehensive information because of low polymorphism, long juvenile phase, and vulnerability to environmental effects like oil palm. Based on this background, this study was carried out to evaluate the genetic diversity and heritability among 26 families of MPOB-Senegal oil palm germplasm using quantitative traits (yield, bunch quality, and vegetative traits) and microsatellite (SSR) molecular markers, in order to identify superior families for future oil palm breeding program and development of DP planting materials. Data on yield components, bunch quality, and vegetative traits were collected for eight consecutive years and were subjected to analysis of variance and multivariate analysis. The analysis of variance showed significant variability among the families for most of the traits evaluated. The mean nut weight and rachis length had high broad-sense heritability value of 62.15% and 61.06%, respectively while the rest of the traits ranged from moderate to low. The 26 families were grouped into six major clusters at the similarity coefficient of 0.72 based on quantitative traits with the aid of unweighted pair group method with arithmetic mean (UPGMA) dendrogram. This finding revealed that MPOB-Senegal germplasm exhibited the important economic traits namely, high kernel to fruit (KTB), kernel to bunch (KTB) and kernel yield (KY), small petiole cross section (PCS) and short rachis length (RL) which are vital for oil palm improving program. Based on the results, the three families SEN02.05, SEN05.02 and SEN06.01 were identified as prospective families for high kernel content which could be the most essential sources of lauric acids for oleochemical industry. Moreover, five families namely, SEN05.02, SEN03.07, SEN02.05, SEN07.05 and SEN10.03 were also recognized as prospective families which could be utilized to breed for the compact palm materials. In the molecular characterization, out of 72, a total 35 highly polymorphic and reproducibility markers were selected for genotyping study. The percentage of polymorphism (P=96.26%), number of effective allele (Ne = 2.653), observed heterozygosity (Ho = 0.584), expected heterozygosity (He = 0.550), total heterozygosity (HT = 0.666), and rare alleles (54) were observed which indicates that MPOB-Senegal germplasm has a broad genetic variation. Among the SSR markers employed, sMo00053 and sMg00133 were recommended as the most informative markers for the MPOB-Senegal oil palm germplasm due to discrimination power in detection of both the highest private and rare alleles. The prevalence of private alleles was high in the SEN05.03, SEN12.03, SEN 3.07 and SEN10.3 families. High rare alleles was observed in SEN07.05, SEN12.03, SEN03.07, SEN06.08 and SEN10.03 families, while the highest observed heterozygosity (Ho) and expected heterozygosity (He) was recorded in SEN06.08 and SEN05.05, respectively. The oil palm populations with high rare alleles and He should be taken into account in selection and conservation, because these populations may have interesting and unique genes to be exploited further. This study identified that MPOB-Senegal germplasm had a broad genetic variation and revealed that the oil palm genetic materials from this germplasm possess very important and useful genetic resources which can broaden the narrow genetic base of current planting materials in terms of high kernel content.